2022
DOI: 10.1038/s41420-022-01144-9
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA NONMMUT015745 inhibits doxorubicin-mediated cardiomyocyte apoptosis by regulating Rab2A-p53 axis

Abstract: Doxorubicin (DOX) is an efficacious and widely used drug for human malignancy treatment, but its clinical application is limited due to side effects, especially cardiotoxicity. Our present study revealed that DOX could induce apoptosis in cardiomyocytes. Herein, we screened the dysregulated long noncoding RNAs (lncRNAs) in DOX-treated cardiomyocytes. Notably, overexpression of lncRNA NONMMUT015745 (lnc5745) could alleviate DOX-induced cardiomyocyte apoptosis both in vitro and in vivo. Conversely, silencing lnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
7
0
2
Order By: Relevance
“…Additionally, DOX-induced oxidative stress stimulates TNF-α release, which activates several signaling pathways containing the nuclear factor kappa B (NF-κβ) inflammatory pathway [ 6 ]. In addition, DOX has a powerful apoptotic effect, where it mainly affects the mitochondrial pathway [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, DOX-induced oxidative stress stimulates TNF-α release, which activates several signaling pathways containing the nuclear factor kappa B (NF-κβ) inflammatory pathway [ 6 ]. In addition, DOX has a powerful apoptotic effect, where it mainly affects the mitochondrial pathway [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies found the role of long non-coding RNA in doxorubicin-induced cardiomyopathy, lncRNA NONMMUT015745 inhibits doxorubicin-mediated cardiomyocytes apoptosis by regulating the Rab2A-p53 axis [27], METTL14 silencing suppresses the ferroptosis of cardiomyocyte in doxorubicin-induced mice[28].TGFB2-AS1 has been reported in breast cancer, glioma, lung adenocarcinoma, gastric cancer, and other tumor diseases, and more importantly, the limited molecular biological role of TGFB2-AS1 in some diseases has been illustrated [29]. Studies have shown that mutations in the TGFBR1 and TGFB2-AS1 genes were associated with myopia in preschoolers, mediated by the TGF-β signaling pathway [30]; loss of TGFB2-AS1 signi cantly promoted Apoptosis of HepG2 liver cancer cells and inhibited migration and invasion [31], and TGFB2-AS1 interacted with the Core subunit of SWI/SNF complex, SMARCA4 to inhibit the expression of target genes TGFB2 and SOX2, ultimately inhibiting the breast Cancer progression [32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that DOX causes apoptosis (Cai et al, 2022). To determine whether GL-PP could prevent DOX-induced cell death, we examined expression of apoptosis-related proteins after GL-PP treatment in cells exposed to DOX.…”
Section: Inhibition Of Dox-induced Mouse Renal Cell Apoptosis By Gl-ppmentioning
confidence: 99%